A man of his own - Wilson, Susan, 1951- (St. Martin's Press, 2013)
Returning home from World War II with injuries that shatter his professional baseball dreams, Rick Stanton's reunited with his beloved dog Pax, who had been volunteered for the Army's K-9 Corps and who's forged an equally strong bond with a soldier who joins Rick's family.